Conceptual Design of a Green Technology Module for Accounting and Sustainable Financial Reporting: An Exploratory Literature-based Study - Dina Rajendra, Ricky (JAF (Journal of Accounting and Finance), 2025)
Rising industrial greenhouse gas emissions have posed critical challenges to the transparency and reliability of corporate carbon emission reporting within financial statements. Efforts to control these emissions are becoming increasingly urgent in line with global commitments to achieving the Sustainable Development Goals (SDGs) 2030 and Net Zero Emissions (NZE) 2060 targets. The integration of technology into financial reporting systems—especially through the Internet of Things (IoT), blockchain, and Artificial Intelligence (AI)—offers concrete solutions for real-time, transparent monitoring, reporting, and verification of carbon emission data. This study aims to develop a Green Technology Module that integrates the Internet of Things for real‑time emissions monitoring, a permissioned blockchain ledger for secure and immutable data storage, and artificial intelligence for emissions analysis and forecasting. A qualitative descriptive method with a literature study approach was employed to examine digital technology integration in sustainable accounting. Findings indicate that the proposed module significantly enhances reporting accuracy and timeliness, bolsters stakeholder confidence through a tiered dashboard which is supported by stakeholder theory, and supports carbon trading processes and adherence to green reporting standards. In conclusion, implementing this module can accelerate sustainable development goals while optimizing both environmental and economic performance of firms. Future research should explore the development of standardized frameworks for the integration of IoT, blockchain, AI technologies into carbon emission accounting and sustainable financial reporting to assess implementation challenges, digital capacity needs, and strengthening multi-stakeholder collaboration frameworks. Keyword: Green Accounting; Sustainable Finance; Artificial Intelligence; Green Blockchain; Internet of Things.